1991
DOI: 10.2527/1991.692478x
|View full text |Cite
|
Sign up to set email alerts
|

Age adjustment factors, heritabilities and genetic correlations for scrotal circumference and related growth traits in Hereford and Brangus bulls.

Abstract: Field data records on 10,511 Hereford and 2,522 Brangus bulls between 330 and 430 d of age were analyzed to find age of calf and age of dam adjustment factors for yearling scrotal circumference. Age of calf adjustment factors were .024 cm/d for Hereford bulls and .041 cm/d for Brangus bulls. Sons of Hereford dams were adjusted to a 6- to 8-yr dam age basis by adding .7, .3, .2, .2 or .3 cm for dams 2, 3, 4, 5 or 8 or more years old, respectively. Age of dam adjustment factors for Brangus bulls were .8, .4, .3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
6
7

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 0 publications
8
42
6
7
Order By: Relevance
“…Brinks (1994) reported that growth of bulls from birth to yearling was positively correlated with SC, but BW had low association with SC. Kriese et al (1991) estimated the phenotypic correlations between BW and 365-day weight in Hereford (r=0.42) and Brangus (r=0.34) bulls, which were similar with the results reported in this study.…”
Section: Resultssupporting
confidence: 81%
“…Brinks (1994) reported that growth of bulls from birth to yearling was positively correlated with SC, but BW had low association with SC. Kriese et al (1991) estimated the phenotypic correlations between BW and 365-day weight in Hereford (r=0.42) and Brangus (r=0.34) bulls, which were similar with the results reported in this study.…”
Section: Resultssupporting
confidence: 81%
“…Poucos são os resultados encontrados na literatura. KNIGHTS et al (1984), BOURDON e BRINKS (1986), KRIESE et al (1991), LÔBO et al(1994) e BERGMANN et al(1996 obtiveram correlação positiva entre PE e características de crescimento e BOURDON e BRINKS (1982), correlação negativa entre DG e características de crescimento, exceto para peso ao nascer. Assim, esperar-se-ia que o PE fosse negativamente correlacionado com a DG, como foi encontrado na presente análise.…”
Section: Resultsunclassified
“…O perímetro escrotal (PE) vem sendo utilizado como critério de seleção, por ter correlações genéticas favoráveis com características de sêmen (KNIGHTS et al, 1984), com idade à puberdade em machos e fêmeas (BOURDON e BRINKS, 1986;MARTIN et 1677 PEREIRA et al al., 1992;e MOSER et al, 1996) e características de crescimento (KNIGHTS et al, 1984;BOURDON e BRINKS, 1986;KRIESE et al, 1991;LÔBO et al, 1994;e BERGMANN et al, 1996). Autores como MACKINONN et al (1990) sugeriram que os fatores hormonais responsáveis pelo desenvolvimento testicular inicial nos machos são os mesmos que promovem o desenvolvimento ovariano inicial nas fêmeas.…”
Section: Introductionunclassified
“…Dentro deste período de estudo da CE, algumas considerações são apresentadas, sobre esta caracterís-tica, para propósitos de reprodução e melhoramento: a) A CE tem sido avaliada considerando a idade de 12 (MOURA e ERICKSON, 1996) ou 18 meses, ou intervalos de medidas repetidas, em que valores adjacentes são mais correlacionados. Alguns exemplos deste último tipo de avaliação são: dos 368 a 400 dias (KING et al, 1983), 205 e 365 dias (TOELLE e ROBISON, 1985), 608 a 852 dias (COULTER et al, 1987), 300 a 400 dias (LUNSTRA et al, 1988), 330 e 430 dias (KRIESE et al, 1991), cinco avaliações com intervalo de 28 dias pós-desmame (PRATT et al, 1991), 12, 18 e 24 meses (ALENCAR et al, 1993), 9, 18, 24 e 30 meses (QUIRINO et al, 1996) e 10 a 30 meses (FREITAS et al, 1997). b) Em cada idade, a CE parece ser controlada por fatores fisiológicos diferentes: hormônios, até atingir a maturidade (24 meses), e o desenvolvimento corporal propriamente dito, que resulta em aumento de peso (até 30 meses).…”
Section: Rev Bras Zootecunclassified